2014
DOI: 10.3352/jeehp.2014.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Incentive structure in team-based learning: graded versus ungraded Group Application exercises

Abstract: Purpose:Previous studies on team-based learning (TBL) in medical education demonstrated improved learner engagement, learner satisfaction, and academic performance; however, a paucity of information exists on modifications of the incentive structure of “traditional” TBL practices. The current study investigates the impact of modification to conventional Group Application exercises by examining student preference and student perceptions of TBL outcomes when Group Application exercises are excluded from TBL grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…A second issue was around the value of the ungraded application activities. This has also been reported in the literature, and a recent review highlighted that grading or ungrading application activities did not influence overall student performance but graded activities clearly added to students' anxiety levels (Deardorff et al 2014). These more negative perceptions of team-based learning emphasise the importance of ensuring students are well prepared for the requirements of team-based learning, and in particular how to use the study resources.…”
Section: Discussionmentioning
confidence: 61%
“…A second issue was around the value of the ungraded application activities. This has also been reported in the literature, and a recent review highlighted that grading or ungrading application activities did not influence overall student performance but graded activities clearly added to students' anxiety levels (Deardorff et al 2014). These more negative perceptions of team-based learning emphasise the importance of ensuring students are well prepared for the requirements of team-based learning, and in particular how to use the study resources.…”
Section: Discussionmentioning
confidence: 61%
“…Numerous studies have shown the benefits of this mode of active learning as a powerful tool to ingrain in-depth knowledge and increase comprehension of the topic (12,13). Vasan in his study on TBL in Anatomy and Embryology concluded such sessions improve student commitment towards course content.…”
Section: Discussionmentioning
confidence: 99%
“…The incentive structure for TBL is a critical component of the learning process and has being the subject of many recent studies . For instance, some authors have suggested that ungraded TBL application exercises could be more student‐friendly while still supporting an active learning environment that fosters development of teamwork skills . Nevertheless, ungraded RATs have been shown to be associated with poor TBL performance as compared to graded RATs .…”
Section: Discussionmentioning
confidence: 99%